A composição da dívida pública mobiliária federal interna e os fundos de investimento no Brasil: análise dos fatores de influência - Rodrigues, Manoel Aparecido (2005)
This work intends to study the relationship between Brazilian Internal Public Debt mix and Mutual Funds. In the theoretical framework, the discussion about liquidity preference theories implies considering risk averse investors. Portfolio selection is also discussed, particularly Markowitz efficient frontier. Historical data from November of 1999 to December of 2004 of Brazilian Internal Public Debt mix and Mutual Funds portfolio are analyzed. Official goals concerning Public Debt's mix and its actual composition are presented, as well as Mutual Fund preferences as buyers of public debt securities. Time series of three securities (LFT, LTN and NTN-C) in Public Debt mix and Mutual Funds portfolio are compared and a similar behavior is identified. Relevant facts of the macroeconomic context which may have affected Public Debt or Mutual Funds are discussed. Some indications of a possible influence of Mutual Funds upon Public Debt Mix are obtained and hypothesis to be tested in future studies are proposed.